2022
DOI: 10.1111/1758-5899.13112
|View full text |Cite
|
Sign up to set email alerts
|

The UN High‐Level Political Forum on Sustainable Development: An orchestrator, more or less?

Abstract: The UN High‐level Political Forum on Sustainable Development (HLPF) is at the heart of the UN's follow‐up and review of the 2030 Agenda and the Sustainable Development Goals (SDGs). Analysing the first full cycle of the HLPF (2016–19), we ask what and how the HLPF delivers. In the early debates on its mandate, experts suggested that the HLPF could be an orchestrator, arguing that it would likely have to rely upon indirect and non‐hierarchical forms of governance. Others asked for more or expected less. For the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…This brings us to some policy recommendations how to enhance the effectiveness of the SDGs and foster sustainable development worldwide. First, the periodic review mechanism taking place at the High‐Level Political Forum on Sustainable Development needs to be strengthened and further developed (Beisheim & Fritzsche, 2022). Second, learning among public and private actors for SDG implementation should be fostered at all levels and scales (Andonova et al, 2022; Türkeli et al, 2020) with large potential for cities and local governments to function as transmission belts between the 2030 Agenda for Sustainable Development and actions on the ground (Hickmann, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This brings us to some policy recommendations how to enhance the effectiveness of the SDGs and foster sustainable development worldwide. First, the periodic review mechanism taking place at the High‐Level Political Forum on Sustainable Development needs to be strengthened and further developed (Beisheim & Fritzsche, 2022). Second, learning among public and private actors for SDG implementation should be fostered at all levels and scales (Andonova et al, 2022; Türkeli et al, 2020) with large potential for cities and local governments to function as transmission belts between the 2030 Agenda for Sustainable Development and actions on the ground (Hickmann, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Power relations between states are also an emerging research topic. Research suggests that conflict lines from other arenas of international cooperation act as barriers to reforms of the HLPF (Beisheim, 2021) and that contested understandings of key terms in the 2030 Agenda are a barrier to implementation (Taggart, 2022). Nevertheless, early scholarly assessments of the 2030 Agenda have suggested that the SDGs mainly reflect a 'traditional' cooperation regime, aimed to maintain legitimacy of the United Nations system and multilateral institutions as enablers of Western interests and imperial power (Caria, 2022;Vogt, 2022).…”
Section: Current Research Trendsmentioning
confidence: 99%
“…Research has taken a critical stance on the orchestration efforts of the HLPF constrained by political conflicts and a lack of resources (e.g. Qerimi, 2022), and explored whether this institution stimulates inter-institutional and cross-level governance (Beisheim & Fritzsche, 2022). Additionally, the contribution and impact of other actors and governance arrangements, such as regional organizations (e.g.…”
Section: Scoping Reviewmentioning
confidence: 99%
“…For this purpose, the UN High-level Political Forum on Sustainable Development, which reviews progress on the existing goals and targets, must evolve into a mechanism that over time also adjusts these targets to the exigencies of multiple global crises. Governments should view this process as an opportunity for more effective peer learning, leveraging synergies, tackling trade-offs, and overall increasing ambition (6). During this regular adjustment process, the role of global scientific assessments in reviewing the adequacy of SDG targets needs to be strong.…”
Section: Dynamizationmentioning
confidence: 99%